(3MSf GdSeJ aj GdUeJs - (3YHO GdQMef Hf CHj HcQ Hf eMeO GdNVjQj GdSjhWj, CHh GdaVd , LdGd GdOjf , J (B911 (3g`s; (3GHf CHj GdOfjG , CHh HcQ YHO Gddg Hf eMeO Hf YHjO Hf SajGf GHf CHj GdOfjG GdbQTj GdCehj,J (B281 (3g` s ((3YHO Gddg Hf YHO GdhGMO Hf YHO GddWja Hf TYjH Hf YHO GdSdGe GdYHGSi s)
(3ChdgG (B:s
(3gPG LRA dNUJg ef cJGH GdUeJ dCHi HcQ Hf CHj GdOfjG hSejJg MSf GdSeJ ai GdUeJ hGddg Gdehab CNQLgG CMeO hGdOQGei s
(3BNQgG (B:s
(3hEf dGefi dGFe ai GdUeJ bdJ dg MHS GdaJi eWbg MQR ef GdfOe JeJ GdQSGdI s
(3Vef eLehY , JQJjHgG (B: (3GdcJGH (B11s
(3HgG Jedc HGSe YHO Gddg Hf YHO GdhGMO Hf YHO GddWja Hf TYjH Hf YHO GdSdGe hjQLY JGQjNgG Edi SfI (B1294 (3g`s
(3HgG fXGe GdJYbjHIs
(3hQO ai cTa GdXfhf ai L(B2 (3U` (B1433 (3Cf cJGH GdUeJ Yh deDdaI CHh HcQ Hf CHj GdOfjGs
(3bQf GdfSN (B:s
(3GdbQf GdKGdK YTQs
(3JHUQI GdYfhGf (B:s
Keywords: (3GdeLGejYs